Pembelajaran Proyek dengan Memanfaatkan Barang Bekas dalam Mendorong Partisipasi dan Karakter Sains Mahasiswa - Siti Fatimah; Oky Ristya Trisnawati (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This study aims to analyze the participation and character of students' science in learning science through project learning based on scraps utilisation during online learning. This research is a qualitative research with 25 students as research subjects. The instrument used is an observation dan interview sheet. The results of the analysis show that learning science by scraps utilisation as learning media can be used to develop student participation and scientific character.